2019
DOI: 10.26737/jetl.v4i2.1322
|View full text |Cite
|
Sign up to set email alerts
|

Self-Concept, Interest in Becoming a Teacher, Prerequisite Courses: What do the Most Determinant Factors in Microteaching Competencies of Prospective Teachers?

Abstract: Self-concept, interest, learning motivation, and prerequisite knowledge potentially contributes to academic achievement. The aim of this study was to determine the relationship between self-concept, interest in becoming a teacher, academic achievement of prerequisite courses and prospective teachers’ competencies of microteaching. This correlational study involved 105 sixth semester students of science department in Education and Teacher Training Faculty (FKIP) of Pontianak, Tanjungpura University. The data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In particular, sentiment expression in the forum related to the quantitative analysis activity (EA2) was linked with the most-negative climate for both cohorts. This task is usually considered as the most difficult by trainee teachers, with participants perceiving themselves as less competent and, consequently, sharing less-positive sentiments, in line with previous results (Djudin, 2019 ). Hence, participants’ preparation or self-regulation prior to the task was perceived as insufficient by trainees compared with the assignment, thus hampering a positive collaborative experience, in line with Bakhtiar et al ( 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…In particular, sentiment expression in the forum related to the quantitative analysis activity (EA2) was linked with the most-negative climate for both cohorts. This task is usually considered as the most difficult by trainee teachers, with participants perceiving themselves as less competent and, consequently, sharing less-positive sentiments, in line with previous results (Djudin, 2019 ). Hence, participants’ preparation or self-regulation prior to the task was perceived as insufficient by trainees compared with the assignment, thus hampering a positive collaborative experience, in line with Bakhtiar et al ( 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…According to Slameto, learning readiness is the entire condition of a person to be ready to respond to situations in a certain way. The questionnaire results on this indicator obtained an average result of 85.71% (Djudin, 2019). The factors for the formation of readiness include: 1) Physiological growth and equipment, such as the body, the five senses, and intellectual capacities; and 2) Motivation is related to one's needs, interests, and various goals for a person to develop and defend themselves.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained correlation coefficient (rxy) was 0.324, and the calculated tcount = 2,81 > ttable = 2,00. Djudin (2019) showed a significant relationship between prerequisite courses and students' ability to conduct microteaching. The analysis found that selfconcept, interest in becoming a teacher, and academic achievement in prerequisite courses significantly correlated with prospective teachers' competence in microteaching.…”
Section: Demonstrated a Correlation Between Cumulative Grade Point Av...mentioning
confidence: 98%
“…Astuti (2018) found that: 1) micro-teaching ability is significantly related to PPL practice; 2) interest in becoming a teacher is positively correlated with micro-teaching ability and PPL practice, and 3) the determination index of micro-teaching and interest in becoming a teacher on PPL practice is 7.50%. The research by Djudin (2019) showed a significant relationship between prerequisite courses and students' ability to perform micro-teaching. The analysis revealed that self-concept, interest in becoming a teacher, and academic achievement in prerequisite courses are significantly associated with the micro-teaching competence of prospective teachers.…”
Section: Introductionmentioning
confidence: 99%